2012
DOI: 10.31357/jtfe.v2i2.592
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos-induced Histopathological Alterations in Duttaphrynus melanostictus (Schneider 1799) Tadpoles: Evidence from Empirical Trials

Abstract: This paper reports the histopathological responses of the gill, liver and tail muscle tissues in tadpoles of the Asian Common Toad Duttaphrynus melanostictus (Schneider, 1799) exposed to chlorpyrifos a common organophosphorus pesticide. Tadpoles of Gosner stages 24-26 were continuously exposed to low, mid and high (500, 1000 and 1500 µgl -1 ) concentrations of chlorpyrifos for two weeks. Histological alterations in the tissues of the surviving larvae were microscopically examined both at the end of the exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The dilation and congestion of blood vessels and sinusoid were one of the most evident results of pyrimethanil application. Similar findings were reported in several amphibian species after exposure to both pesticides and heavy metals 34 , 53 , 54 . Some authors suggested that endothelial cells alterations may affect the blood flow from the hepatic artery and veins to the central vein thus resulting in extravasations of red blood cell and sinusoids dilation 53 , 55 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The dilation and congestion of blood vessels and sinusoid were one of the most evident results of pyrimethanil application. Similar findings were reported in several amphibian species after exposure to both pesticides and heavy metals 34 , 53 , 54 . Some authors suggested that endothelial cells alterations may affect the blood flow from the hepatic artery and veins to the central vein thus resulting in extravasations of red blood cell and sinusoids dilation 53 , 55 .…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were reported in several amphibian species after exposure to both pesticides and heavy metals 34 , 53 , 54 . Some authors suggested that endothelial cells alterations may affect the blood flow from the hepatic artery and veins to the central vein thus resulting in extravasations of red blood cell and sinusoids dilation 53 , 55 . We also showed a remarkable liver tissue dyschromia highlighting the establishment of different pathologic response in the same tissue.…”
Section: Discussionsupporting
confidence: 87%
“…Exposure to chlorpyrifos led to smaller body sizes and delayed maturation in Rana boylii tadpoles (Sparling and Fellers 2009). Moreover, it induces histopathological changes in the gills, liver, and tail of tadpoles of the Duttaphrynus melanostictus species (Bandara et al 2012). Chlorpyrifos is usually found in agricultural areas and may directly affect aquatic ecosystems.…”
Section: Chlorpyrifos Concentrations In H Rugulosus Samplesmentioning
confidence: 99%
“…In Sri Lanka, it is found all over the country and occurs up to elevations of about 1700 m (Manamendra-Arachchi and Pethiyagoda, 2006). It is more abundant in human altered habitats such as agricultural landscapes and urban settings (Bandara et al, 2012). Duttaphrynus melanostictus is distinguished from all the other Sri Lankan Duttaphrynus species because of the absence of parietal ridges and the presence of two longitudinal rows of large warts which distributed all length of inter parotid area.…”
Section: Test Animalmentioning
confidence: 99%